Combined effect of rainfall and sunshine duration on cassava output in Nigeria - O. D. ABERJI; G. E. OYITA; S. ENWA (Journal of Agrometeorology)
This study examined the combined effect of rainfall and sunshine duration on Casava production in Nigeria from 1988 to 2023 using secondary data obtained from the Nigeria Meteorological Agency (NiMet) and the Food and Agriculture Organization (FAO). Econometric techniques were employed to analyse the relationships between the variables. Regression analysis revealed that cassava yield was significantly negatively related with rainfall (β = -73,133.9; p = 0.000), while sunshine duration was positive and significant (β = 8,755,640.3; p = 0.000). Rainfall and sunshine duration interaction was significant and positive (β = 7,611.8; p = 0.000) and revealed that sunshine duration was mediating the adverse effect of excessive rainfall. The model explained a high explanatory power with R-squared being 0.896 and adjusted R-squared being 0.881. The error correction model (ECM) coefficient (-0.934) showed a high speed of adjustment towards equilibrium, which meant that the deviations in the output of cassava as a result of climate variability were adjusted quickly. Based on the findings of this study, farmers are encouraged to adopt water management practices and improved agronomic practices in an attempt to enhance the positive effects of sunshine duration on cassava yield.